Assessing small and medium-size enterprise CEOs' attitude towards business growth: the impact of event risk - Yuksel Ekinci; Padmali Rodrigo; Arnold Japutra; Sertaç Çifci; Mcxin Tee; Ye Jia (Journal of Business Economics and Management)
This research explores SME CEOs’ attitudes toward business growth during extreme global event risks, addressing the gap in understanding SME growth strategies in times of global crises. Drawing from Protection Motivation Theory, Theory of Planned Behaviour, and Resource-Based View, conceptual framework was developed to investigate how motivating factors impact SME CEOs’ attitude and commitment towards business growth intention, with company size as moderator. Data were collected through an online survey administered to 198 Turkish SME CEOs and analysed using structural equation modelling. The results demonstrate that SME CEOs’ intention is influenced by attitude toward business growth, growth commitment, and perceived event risk. Company size only moderates the relationship between event risk and business growth intention. Subjective norms positively influence the attitude toward business growth. Interestingly, there is no relationship between perceived behavioural control and attitude. This study provides better understanding of SME growth decisions during crises, offering insights for both scholars and practitioners. It highlights that practitioners should be aware that business growth decisions are influenced by perceived expectations from others, internal motivations, organisational factors, and external factors (e.g., event risk). The findings suggest that SME CEOs need to be more agile and proactive in responding to external event risk.